KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL (EQ) DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMPIT RIYADHUSSOLIHIIN - Muhamad Habibbullah (UNISAN JURNAL, 2023)
Therefore the researchers tried to analyze the leadership of the chairman of the Institute of Education Institutions SMPIT Riyadhussolihiin focused from the point of view of his emotional intelligence. This research is a qualitative research that describes the leadership of the Chairman of the Institute of Education Institutions SMPIT Riyadhussolihiin and analyze the point of view of emotional intelligence. This research was conducted with observation, interview and documentation techniques. Testing the validity of the data using triangulation techniques, which in this study is more emphasized to triangulation techniques sources. The source is all citizens of the good foundation of board, environment, people around including teachers in elementary, junior high and vocational school SMPIT Riyadhussolihiin . The source will contain the leadership data of the chairman of the SMPIT Riyadhussolihiin Foundation based on emotional intelligence. The results showed that, chairman of the foundation SMPIT Riyadhussolihiin have good leadership regarded from the angle of emotional intelligence. The results of the analysis show that the chairman of the foundation runs a primal leadership leadership very well. It is proven by triangulation of data and source. Chairman of the SMPIT Riyadhussolihiin Institute of Educational Institutions Intercession Tulang Bawang has a high commitment to the future vision, especially during times of stress or in the midst of increasing responsibility. The chairman of the foundation takes an emotional approach to all citizens within the foundation. The Chairman of the Foundation is able to read his own emotions and recognize their impact using instinct to guide decisions, know their strengths and limitations, be able to control emotions and show honesty and integrity, trustworthiness. Chairman of the Foundation has self-awareness and good self- management, good social awareness and good relations management.